2008
DOI: 10.1016/j.dsr2.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Primary, new and export production in the NW Pacific subarctic gyre during the vertigo K2 experiments

Abstract: This paper presents results on tracer experiments using 13 C and 15 N to estimate uptake rates of dissolved inorganic carbon (DIC) and nitrogen (DIN).Experiments were carried out at station K2 (47°N, 161°E) in the NW Pacific subarctic gyre during July-August 2005. Our goal was to investigate relationships between new and export production. New production was inferred from the tracer experiments using the f ratio concept (0-50m); while export production was assessed with neutrally buoyant sediment traps (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 44 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The open square indicates that no N 2 fixation was detected. Data for N 2 fixation measurements at various stations are from Dore et al [2002], Montoya et al [2004], Voss et al [2006], Needoba et al [2007], Garcia et al [2007], White et al [2007], Chen et al [2008], Elskens et al [2008], Moutin et al [2008], Grabowski et al [2008], Church et al [2009], and Bonnet et al [2009]. Background contour indicates nitrate concentrations ( μM ) in the surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…The open square indicates that no N 2 fixation was detected. Data for N 2 fixation measurements at various stations are from Dore et al [2002], Montoya et al [2004], Voss et al [2006], Needoba et al [2007], Garcia et al [2007], White et al [2007], Chen et al [2008], Elskens et al [2008], Moutin et al [2008], Grabowski et al [2008], Church et al [2009], and Bonnet et al [2009]. Background contour indicates nitrate concentrations ( μM ) in the surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…Our result was coincident with that. Elskens et al [27] found 3.7-4.3 mmol C·m −2 ·d −1 of new production were remineralized from 50-150 m in the northern Pacific according to carbon mass balance. Dehairs et al [28] estimated that the POC remineralization fluxes varied between 1.0-8.8 mmol C·m −2 ·d −1 in the northern Pacific.…”
Section: Pom Remineralizationmentioning
confidence: 98%
“…; Table 5). Furthermore, for K2, we chose to parameterize the model with an initial PT immediately below the euphotic zone, given the shallow euphotic zone and some evidence from 234 Th and nutrient budgets of significant remineralization between 50 and 150 m (Buesseler et al 2008b;in press;Elskens et al 2008). At depths below this initial PT, we used a longer PT length scale (150 m) due to the larger size of zooplankton fecal pellets at K2 relative to ALOHA, which, along with their higher mineral content, would increase sinking rates (Buesseler et al 2007b;Wilson et al 2008).…”
Section: Discussionmentioning
confidence: 99%